Assessment of the Deep Sea Wreck USS Independence - Delgado, James P.; Symons, Lisa C.; Elliott, Kelley; Cantelas, Frank; Schwemmer, Robert V. (Frontiers in Marine Science, 2016)
As part of ongoing efforts to better understand the nature of shipwrecks in National Marine Sanctuaries which may pose some level of pollution risk, and in this case, to definitively locate what is likely the only shipwreck in a sanctuary involved in both nuclear testing and nuclear waste disposal, NOAA’s Office of National Marine Sanctuaries collaborated with NOAA’s Office of Ocean Exploration and The Boeing Company, which provided their autonomous underwater vehicle, Echo Ranger, to conduct the first deep-water archaeological survey of the scuttled aircraft carrier USS Independence in the waters of Monterey Bay National Marine Sanctuary (MBNMS) in March 2015. The presence of the deep-sea scuttled “radioactive” aircraft carrier USS Independence off the California coast has been the source of consistent media speculation and public concern for decades. The survey confirmed that a sonar target charted at the location was Independence, and provided details on the condition of the wreck, and revealed no detectable levels of radioactivity. At the same time, new information from declassified government reports provided more detail on Independence’s use as a naval test craft for radiological decontamination as well as its use as a repository for radioactive materials at the time of its scuttling in 1951. While further surveys may reveal more, physical assessment and focused archival work has demonstrated that the level of concern and speculation of “danger” from either a radioactive or oil pollution threat posed may be exaggerated.